Do statins improve outcomes and delay the progression of non-rheumatic calcific aortic stenosis?. Issue 7 (26th January 2011) - Parolari, Alessandro; Tremoli, Elena; Cavallotti, Laura; Trezzi, Matteo; Kassem, Samer; Loardi, Claudia; Veglia, Fabrizio; Ferrari, Giovanni; Pacini, Davide; Alamanni, Francesco
Abstract : Context: It is not known whether statin treatment improves clinical outcomes and reduces aortic stenosis progression in non-rheumatic calcific aortic stenosis. Objective: A meta-analysis of studies was performed comparing statin therapy with placebo or no treatment on outcomes and on aortic stenosis progression echocardiographic parameters. Data sources: The authors searched Medline and Pubmed up to January 2010. Data extraction: Two independent reviewers independently abstracted information on study design (prospective vs retrospective or randomised vs non-randomised), study and participant characteristics. Fixed and random effects models were used. A-priori subanalyses assessed the effect of statins on low-quality (retrospective or non-randomised) and on high-quality (prospective or randomised) studies separately. Results: Meta-analysis identified 10 studies with a total of 3822 participants (2214 non-statin-treated and 1608 statin-treated); five studies were classified as prospective and five as retrospective; concerning randomisation, three trials were randomised whereas seven were not. No significant differences were found in all-cause mortality, cardiovascular mortality or in the need for aortic valve surgery. Lower-quality (retrospective or non-randomised) studies showed that, in statin-treated patients, the annual increase in peak aortic jet velocity and the annual decrease in aortic valve area were lower, but this was not confirmed by the analysis in high-quality (prospective or randomised) studies. Statins did not significantly affect the progression over time of peak and mean aortic gradient. Conclusions: Currently available data do not support the use of statins to improve outcomes and to reduce disease progression in non-rheumatic calcific aortic valve stenosis.